The B side : the death of Tin Pan Alley and the rebirth of the great American song - Yagoda, Ben (New York : Riverhead Books, a member of Penguin Group (USA), 2015)
An acclaimed cultural historian--drawing on previously untapped archival sources and interviews with such voices as Randy Newman, Jimmy Webb, Linda Ronstadt, and Herb Alpert--presents a social history of the great American songwriting era.
"Everybody knows and loves the American Songbook. But it's a bit less widely understood that in about 1950, this stream of great songs more or less dried up. All of a sudden, what came over the radio wasn't Gershwin, Porter, and Berlin, but "Come on-a My House" and "How Much Is That Doggie in the Window?" Elvis and rock and roll arrived a few years later, and at that point the game was truly up. What happened, and why? In The B Side, acclaimed cultural historian Ben Yagoda answers those questions in a fascinating piece of detective work. Drawing on previously untapped archival sources and on scores of interviews--the voices include Randy Newman, Jimmy Webb, Linda Ronstadt, and Herb Alpert--the book illuminates broad musical trends through a series of intertwined stories. Among them are the battle between ASCAP and Broadcast Music, Inc.; the revolution in jazz after World War II; the impact of radio and then television; and the bitter, decades-long feud between Mitch Miller and Frank Sinatra. The B Side is about taste, and the particular economics and culture of songwriting, and the potential of popular art for greatness and beauty. It's destined to become a classic of American musical history" --
Premises, premises -- Mr. Miller and Mr. Schwartz, 1954 -- I get a kick out of you, 1885-1933 -- Jukebox Saturday night, 1925-1942 -- As time goes by, 1941-1948 -- What happened to the music?, 1946-1954 -- Brill Building boys, and girl, 1950-1955 -- The big beat, 1951-1968 -- Fly me to the moon, 1939-1965 -- Do you believe in magic?, 1957-1965.
Includes bibliographical references (pages 286-291) and index.
Keywords: Popular music -- United States -- History and criticism; Popular music -- Writing and publishing -- United States -- History and criticism